The structure of white-collar compensation and organizational performance - O'Shaughnessy, K. C. (Relations industrielles / Industrial Relations, 1998)
Using a unique data set, this paper analyzes how the relationship between managerial compensation and firm performance changes as one moves down the organizational hierarchy. It is found that predictions of efficiency wage, agency, and tournament models of compensation differ for different hierarchical levels in organizations. The results add support to the notion that a variety of models may be necessary to explain organizational compensation strategies.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Compensation plans; Correlation analysis; Executive compensation; Executives; Hypotheses; Labor Unions; Performance; Salaries pensions etc; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; White collar workers